ASSIMILATION OF THE ECOLOGICAL COMPONENT IN CHEMISTRY WITH THE HELP OF INFORMATION TECHNOLOGIES - Pylypchuk , Liudmyla; Volkova , Svitlana; Popovych , Tetiana; Reshnova , Svitlana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article discusses some ways of using the latest information technologies in the greening of the study of the chemical components of education.